Posted by **Sydney** on Saturday, July 25, 2009 at 8:59pm.

I'm working on vertical asymptotes when factoring 6x^2 - 6 (denominator). I came up with 6(x^2-1). Then I was trying to find the zeros of the denominator but 6 does not = 0 and x^2-1=0 then I got x^2=1 and x = plus or minus sqrt 1. Can you tell me what I am doing wrong?

- College Algebra -
**MathMate**, Saturday, July 25, 2009 at 11:10pm
(6x²-6)

=6(x²-1)

=6(x+1)(x-1)

If the above expression is the denominator of a given function, there will be two vertical asymptotes, namely at the zeroes of the given expression, at x=1 and x=-1.

The expression equals zero at these two places since 6*0=0.

## Answer This Question

## Related Questions

- pre cal - g(x) = x^2 - x -12 / x + 1 I know the division brings it to x -2 + -10...
- College Algebra - Using the 7 steps outlined in section 4.3 of your book, ...
- Math - State domain, range, period, vertical asymptotes, zeros, symmetry and y-...
- algebra - Create a rational function with a linear binomial in both the ...
- ALGEBRA - Create a rational function with a linear binomial in both the ...
- math - the sum of numerator and denominator is 3 less than twice the denominator...
- math - 1)The area A of a triangle varies jointly as the lengths of its base b ...
- math,correction please.. - (x)/(x-2) - (x+1)/(x) = (8)/(x^2-2x) I keep getting x...
- Calculus - Ok so I have to find a vertical asymptote with denominator 3x^3-x-1. ...
- Calculus/College Algebra - I'm so lost. We're working on limits for this ...

More Related Questions